The emerging role of pathologists in the era of modern medicine. - Shovana Karki (Journal of Pathology of Nepal)
In the era of modern medicine, the role of pathologists has become increasingly important and multidimensional. Most pathologists traditionally shielded comfortably behind their microscopes usually in their basement offices with minimum interactions with other clinicians or patients.  The pathologists were mainly involved in the morphological diagnosis which included macroscopic and microscopic examination of received specimens. This slowly changed with pathologists starting fine needle aspirations and core biopsies. Interactions with clinicians improved with multidisciplinary meetings. The first significant change in the role of a pathologist was seen with the advent of immunohistochemistry. The understanding of protein expression on normal and pathologic cells made it possible for nosological classification of neoplasms.1 So with the use of histochemistry pathologists were able to accurately classify neoplasms.